GOVERNMENT STRATEGIES IN INCREASING PUBLIC PARTICIPATION IN GENERAL ELECTIONS - Ade Risna Sari (Adisam Publisher, 2025)
In modern democracies, voter turnout is an important indicator of the health and legitimacy of the system. This research aims to evaluate the government's strategy in increasing voter participation through an in-depth literature review. The results show that inclusive and sustainable voter education can increase people's awareness and understanding of the electoral process and the importance of participation in voting. Voter education is effective in mobilizing younger and underrepresented groups of voters, including women and minorities. Furthermore, strategies to improve accessibility and ease of voting - such as electronic voting technology, more flexible polling location arrangements and the provision of disability-friendly facilities - have been shown to increase voter turnout. Finally, trust in the electoral system is another important factor. The analysis found that transparency of the electoral process and prompt action against indications of fraud can increase public trust, which in turn encourages higher turnout.